Nexus of Gender and Renewable Energy: Importance and Trends in Global and National context - Joshi, Rekha Maskey (Rural Development Journal, 2024)
This is an article on “Nexus of Gender and Renewable Energy: Importance and Trends in Global and National context”. Here, as per objectives of the study, literatures on the respective issues have been reviewed by a desk review process. This paper has highlighted the issues on importance and trends of gender-energy nexus. The reviews have tried to show association between SDG 7: "Ensure access to affordable, reliable, sustainable and modern energy for all.” SDG: 5 is "Achieve gender equality and empower all women and girls" for sustainable development. The major highlight of the paper is effective Policy implication, participation, importance and trends, poverty and energy justice and transitions are inseparable entities of gender energy nexus. Energy access saves time, reduces drudgery, reduces indoor air pollution levels, improves education and improves health of women, alleviates poverty etc. Energy access creates new opportunities for income generating activities.